Propulsion - Kerwin, Justin E. (Justin Elliot); Hadler, Jacques B. (Principles of Naval Architecture series, 2010)
This book presents a comprehensive and up-to-date treatment of propeller analysis and design, including beginning with an introduction to various types of marine propulsion machinery, definitions of powers and efficiencies, and two- and three-dimensional airfoil theory. A section on three-dimensional hydrofoil theory introduces wake vortex sheets and three-dimensional vortex lines. These discussions topics are followed by linear lifting line- and lifting surface theory with both exact and approximate solution methods-including properties of helicoidal vortex sheets, optimum and arbitrary circulation distributions, and the Lerbs induction factor method. There are sections on model testing of propellers, propeller strength and followed by selection and design using both standard series charts and by circulation theory. The final section discusses ship standardization trials, their purpose, measurement methods and instruments, concluding with the analysis of trial data and derivation of the model-ship correlation allowance.